2018
DOI: 10.4183/aeb.2018.213
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the Course Of Gestation and Pregnancy Outcomes in Women with Gestational Diabetes Mellitus

Abstract: Background. Gestational diabetes mellitus (GDM) is associated with high frequency of obstetric complications, such as gestosis, polyhydramnios, urogenital infection, premature birth. An increase in the number of cases of detection of GDM in pregnant women living in Kazakhstan is noted recently. Objective. This research was carried out in order to see the influence of GDM on the course of the third trimester of pregnancy, outcomes and fetal status in women of Kazakh ethnic group. Research design. Cohort observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…At the moment, there are no statistically reliable data regarding the prevalence, guidelines and risk factors for GDM in women living in Kazakhstan [ 210 ].…”
Section: Asiamentioning
confidence: 99%
“…At the moment, there are no statistically reliable data regarding the prevalence, guidelines and risk factors for GDM in women living in Kazakhstan [ 210 ].…”
Section: Asiamentioning
confidence: 99%
“…Preconceptional diabetes is a known risk factor for fetal congenital malformations, including oro-facial clefts (23)(24)(25)(26)(27)(28)(29). It is assumed that in the early stages of pregnancy, the harmful effect of hyperglycemia causes the more frequent occurrence of syndromes and malformations in gestational diabetes, as a direct effect of low control or lack of control during pregnancy.…”
Section: Gestational Diabetes Mellitus and Ocfsmentioning
confidence: 99%
“…Meiramova et al stated that pre-pregnancy BMI was higher, and gestational hypertension rate was higher in the GDM group compared to the control group. They also reported that the rate of cesarean section, birth induction, birth trauma, diabetic fetopathy were significantly higher in the GDM group compared to the control group, and the 5 th minute APGAR score of the newborn was substantially lower (20).…”
Section: Only-dietmentioning
confidence: 95%